Studi Peningkatan Kinerja Manajemen Rantai Pasok Sayuran Dataran Tinggi di Jawa Barat - Alim Setiawan S; Marimin Marimin; Yandra Arkeman; Faqih Udin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
A performance measurement model is a necessary tool for highland vegetables supply chain performance improve- ment in West Java. The performance measurement is conducted to support an objective planning, a performance evaluation, and determination of the future steps in strategical, tactical and operational levels. This study used system approach which is supported by Exponential Comparison Method (ECM) for the selection of superior products; the combination of the SCOR Model with the Fuzzy AHP to design performance metrics; the Data Envelopment Analy- sis (DEA) for performance measurement; and the SWOT analysis to formulate the strategy for increasing the supply chain performance. The result of the ECM showed three commodities with the highest value i.e. Papprica, Lettuce Head and Broccoli. The combined SCOR - Fuzzy AHP analysis produced the performance metric values as follows: delivery performance (0.111), compliance to quality standards (0.299), order fulfillment performance (0.182), order leadtime (0.068), order fulfillment cycle time (0.080), supply chain flexibility (0.052), the SCM cost (0.086), cash-to- cash cycle time (0.080), and the daily stock (0.048). The supply chain performance measurement for Lettuce with the DEA approach indicated that the farmers had not been 100% efficient. While at the company level, the supply chain performance measurement of Lettuce crop and fresh cut showed the efficiency performance of 100 %. Eventually, the SWOT strategy analysis on the Lettuce lead to the following recommendations to improve the performance:1) use hydrophonic cultivation technology and reduce excessive pesticides, 2) optimize the planting and harvesting schedules considering the climate; 3) increase the responsiveness and the flexibility in meeting consumer orders, and 4) imple- ment the required standard quality assurance and management systems to ensure the consistency of the product quality and acceptability by the consumers.ABSTRAKModel pengukuran kinerja sangat diperlukan sebagai alat untuk peningkatan kinerja rantai pasok sayuran dataran tinggi di Jawa Barat. Pengukuran kinerja dapat mendukung perencanaan tujuan, evaluasi kinerja, perumusan kebijakan strategik, taktis dan operasional rantai pasok. Studi ini dilaksanakan dengan pendekatan sistem yang didukung dengan Teknik/Metode Perbandingan Eksponensial (MPE) untuk menyeleksi komoditi prioritas, kombinasi teknik SCOR dan Fuzzy AHP digunakan untuk merancang metrik pengukuran kinerja, Data Envelopment Analysis (DEA) untuk pen- gukuran kinerja individu anggota rantai pasok dan analisis SWOT untuk merumuskan strategi peningkatan kinerja ran- tai pasok. Hasil MPE menunjukkan bahwa 3 (tiga) komoditas yang diunggulkan adalah Paprika, Lettuce dan Brokoli. Kombinasi SCOR - Fuzzy AHP menghasilkan bobot metrik kinerja rantai pasok: kinerja pengiriman (0,111), Kesesua- ian dengan standar kualitas (0,299), kinerja pemenuhan pesanan (0,182), waktu tunggu pesanan (0.068), pemenuhan siklus pesanan (0,080), fleksibilitas rantai pasok (0,052), biaya manajemen rantai pasok (0,086), siklus pembayaran tunai (0,080), dan stok harian (0.048). Pengukuran kinerja rantai pasok komoditi lettuce dengan teknik DEA menun- jukkan bahwa kinerja efisiensi petani belum mencapai 100 %. Kinerja efisiensi perusahaan pada kasus komoditi lettuce dan sayuran segar potong telah mencapai 100%. Analisa SWOT merekomendasikan strategi untuk peningkatan kinerja rantai pasok lettuce sebagai berikut: 1) penggunaan teknologi hidroponik dan pengurangan penggunaan pestisida, 2) optimasi penjadwalan penanaman dan pemanenan dengan memperhatikan iklim, 3) peningkatan fleksibilitas dalam pemenuhan pesanan, dan 4) penerapan standar manajemen penjaminan kualitas untuk menjamin konsistensi kualitas produk dan penerimaan produk oleh konsumen.